1987
DOI: 10.1016/s0022-5347(17)43117-x
|View full text |Cite
|
Sign up to set email alerts
|

Diuresis Renography and Simultaneous Renal Pelvic Pressure in Hydronephrosis

Abstract: We investigated 23 hydronephrotic kidneys in 10 male and 12 female patients (mean age 32 years) with diuresis renography and simultaneous, continuous renal pelvic pressure measurement to compare isotope washout with pelvic pressure changes. No correlation was found between these 2 parameters. Of the kidneys 14 were investigated further by a standard Whitaker pressure flow study. There was only a poor correlation between diuresis renography and the pressure flow study, and between the pelvic pressures during pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…No other study reports such a high frequency (table IB), the highest being 56% [24], Concomitant investigation of pelvis drainage was performed in only four studies. The kidneys, thus found obstructed, were functionally depressed in only 47 % (the range in the different series was 30-80%) of a total of 15 antenatally detected obstructions [63,64], and in no more than 24% (range 21-70%) of totally 181 adult ones [57,60], The relative contribution of the functionally depressed kidneys was usually fairly good: 34% (range 30-39%) in neonates [24], 25% (range 0-40%) in chil dren [24,[79][80][81], and 23% (range 5-39%) in adults…”
Section: Renal Blood Flow and Glomerular Filtrationmentioning
confidence: 86%
See 1 more Smart Citation
“…No other study reports such a high frequency (table IB), the highest being 56% [24], Concomitant investigation of pelvis drainage was performed in only four studies. The kidneys, thus found obstructed, were functionally depressed in only 47 % (the range in the different series was 30-80%) of a total of 15 antenatally detected obstructions [63,64], and in no more than 24% (range 21-70%) of totally 181 adult ones [57,60], The relative contribution of the functionally depressed kidneys was usually fairly good: 34% (range 30-39%) in neonates [24], 25% (range 0-40%) in chil dren [24,[79][80][81], and 23% (range 5-39%) in adults…”
Section: Renal Blood Flow and Glomerular Filtrationmentioning
confidence: 86%
“…These circum stances have led to an intense effort to find measures for sorting out the nonobstructed cases, including pressure/ flow measurements, diuretic urography, diuretic USG, and different diuretic-renogram parameters [47,48], The accuracy of renography [49][50][51] and pressure/flow measurements [51] has been excellent, as related to find ings at operation or the outcome of nonoperative follow up. The match between the different methods of investi gation [52] has varied considerably -from around 60-85% [51,[53][54][55] to around 30% [56,57], Unfortunately, a poor match seems to occur more often in obstructed and equivocal cases than in nonobstructed ones. How ever, since there is no 'golden standard', these investiga tions should be interpreted cautiously and should not be a substitute for old-fashioned, sound clinical judgement (pain, urinary tract infection, palpable mass, and oth ers)!…”
Section: Restriction To Flowmentioning
confidence: 99%
“…Different diagnostic tests have been proposed, e.g. pressure flow investigations [5], di uresis urography [6], diuresis renography [7], However, the picture has become more shaded, as several investi gations have shown that the diagnostic tests often given opposing results [8][9][10][11][12][13] and the view has been advanced that reconstruction based on symptoms and the urographic appearance is feasible without further diagnos tics [14].…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent a MAG 3 renogram and intravenous urogram (IVU) prior to surgery. The accepted indications for surgery were symptoms with a type 2 F + 20 diuresis renogram 3 and an IVU or decreasing function on serial MAG 3 renograms.…”
Section: Methodsmentioning
confidence: 99%